Toward empowered and sustainable tourism MSMEs: a three-level social commerce intervention model - Arfah Sahabudin; Muhammad Ramli; Nabila Rahma Dani; Ananda Reyka Kodao (Universitas Merdeka Malang, 2026)
The digital era offers great potential for tourism MSMEs through social commerce, which blends social media with online transactions. This study develops an adaptive empowerment strategy for tourism MSMEs in developing regions to help them become independent and sustainable. Using a qualitative case study, data were collected from 23 MSMEs across 12 destinations in Polewali-Mandar through interviews, observation, and document analysis. Findings highlight three key points: (1) Digital skills remain low, promotional content is basic, and social commerce tools are underused. (2) There are clear opportunities in social media usage, youth involvement, and community support. (3) A step-by-step mentoring model is needed, tailored to digital readiness levels. The study introduces a Three-Level Social Commerce Intervention Model: Basic digital literacy, Content creation and engagement, and Branding, digital payments, and collaboration. Its novelty lies in integrating phased strategies with strong community roles in digital transformation. This model supports both academic understanding and practical efforts to empower tourism MSMEs in developing regions.